Angiotensin II Receptor–Neprilysin Inhibitor Sacubitril/Valsartan Improves Endothelial Dysfunction in Spontaneously Hypertensive Rats. Issue 10 (17th October 2017) - Seki, Takunori; Goto, Kenichi; Kansui, Yasuo; Ohtsubo, Toshio; Matsumura, Kiyoshi; Kitazono, Takanari
Abstract : Background: We have previously demonstrated that antihypertensive treatment with renin‐angiotensin system inhibitors restores the impaired endothelium‐dependent hyperpolarization (EDH)–mediated responses in spontaneously hypertensive rats (SHRs). Herein, we investigated whether the angiotensin II receptor–neprilysin inhibitor sacubitril/valsartan (LCZ696) would improve reduced EDH‐mediated responses and whether LCZ696 would exert additional effects on endothelium‐dependent and endothelium‐independent vasorelaxation compared with an angiotensin II type 1 receptor blocker alone during hypertension. Methods and Results: SHRs were treated for 3 months with either LCZ696 or valsartan, from the age of 8 to 11 months. Age‐matched, untreated SHRs and Wistar‐Kyoto rats served as controls. Membrane potentials and contractile responses were recorded from the isolated superior mesenteric arteries. Acetylcholine‐induced, EDH‐mediated responses were impaired in untreated SHRs compared with Wistar‐Kyoto rats. EDH‐mediated responses were similarly improved in the LCZ696‐ and valsartan‐treated SHRs. No difference was observed in acetylcholine‐induced, nitric oxide‐mediated relaxations among the 4 groups. Endothelium‐independent relaxations in response to a nitric oxide donor, sodium nitroprusside, and those to levcromakalim, an ATP‐sensitive K + ‐channel opener, were similar among the 4 groups; however, the sensitivities to levcromakalim were significantly higher in both LCZ696‐ and valsartan‐treated SHRs. Conclusions: LCZ696 appears to be as effective as valsartan in improving the impaired EDH‐mediated responses during hypertension. LCZ696 and valsartan exert similar beneficial effects on endothelium‐independent relaxation via enhanced sensitivity of the ATP‐sensitive K + channel. However, the dual blockade of renin‐angiotensin system and neutral endopeptidase with LCZ696 does not appear to provide additional benefit over valsartan alone on vasomotor function in mesenteric arteries of SHRs.